The anti-landscapes of the Arctic: understanding circumpolar sea–land relationships from a Lacanian perspective - Xue Chenru (Edward Elgar Publishing, 2025)
Anti-landscapes are spaces that do not sustain life (Nye, 2014). In the circumpolar regions, the transformation between landscape and anti-landscape occurs both materially and symbolically, shaping the Arctic into a contradictory space. How can the Arctic anti-landscape be understood within the Lacanian triad of three orders? In what ways does the study of anti-landscape offer new perspectives on the wicked problems of the Arctic marine environment? This chapter tries to answer these questions by mobilizing visual culture and human geography, offering an interdisciplinary understanding of Arctic anti-landscape. Through the interpretations of different types of Arctic anti-landscape in the context of industrialism and the Arctic exploration, I tend to seek the potentials to energize the land–sea sustainability of the Arctic regions.
Understanding Marine Changes: Environmental Knowledge and Methods of Research